Evolution of an Accelerated 3-Year Pathway to the MD Degree: The Experience of New York University Grossman School of Medicine. (April 2020) - Cangiarella, Joan; Cohen, Elisabeth; Rivera, Rafael; Gillespie, Colleen; Abramson, Steven
Abstract : The revision of the curriculum at New York University Grossman School of Medicine in 2010, with a reduction of the preclerkship curriculum to 18 months, made it possible to offer an accelerated 3-year pathway in 2013 for students who know their career path. The goals of the program include individualizing education, reducing student debt, and integrating undergraduate and graduate medical education. This accelerated 3-year doctor of medicine (3YMD) pathway is the first program of its kind in the United States to offer conditional acceptance to residency programs in all specialties through the National Resident Matching Program. Since inception of the pathway 6 years ago, 81 students have graduated. Critical components to successfully launch and implement the program are described. Unwavering commitment to the program as a high institutional priority by the dean and vice dean for education facilitated the support required by department chairs and residency program directors and the flexibility needed for success. Alignment between the 3- and 4-year pathways has made it possible to add points of entry into the 3-year pathway during the second and third years and to shift back into the 4-year pathway, as warranted. Modifications to how 3YMD students are mentored included changing the role of the departmental advisor and adding a dedicated 3YMD pathway advisor who serves as an advocate for both the students and the program. Having a relatively large number of 3YMD students has contributed to the success of the program and facilitated acceptance by the residencies. Abstract : Supplemental Digital Content is available in the text.